2001
DOI: 10.1128/aac.45.11.3250-3252.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Efficacy of Telithromycin (HMR3647) against Streptococcus pneumoniae and Haemophilus influenzae

Abstract: The in vivo activity of telithromycin against erythromycin A-and penicillin G-resistant Streptococcus pneumoniae was superior to that of azithromycin, clarithromycin, cefdinir, and levofloxacin. In respiratory tract infections caused by erythromycin A-susceptible S. pneumoniae or Haemophilus influenzae in mice, telithromycin was more effective than clarithromycin and comparable to azithromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…The clarithromycin concentrations in ELF observed in our study could be an underestimation due to dilutional error inherent in the BAL procedure used. However, the ELF concentrations were consistently higher, and coupled with the results from the study by Okamoto et al [11], this provides strong support for the idea that significantly greater intrapulmonary disposition relative to serum exists for clarithromycin in mice, as it does in humans. Additionally, the ability of the bacteria to grow in thigh versus lung tissue may also impact on the results.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The clarithromycin concentrations in ELF observed in our study could be an underestimation due to dilutional error inherent in the BAL procedure used. However, the ELF concentrations were consistently higher, and coupled with the results from the study by Okamoto et al [11], this provides strong support for the idea that significantly greater intrapulmonary disposition relative to serum exists for clarithromycin in mice, as it does in humans. Additionally, the ability of the bacteria to grow in thigh versus lung tissue may also impact on the results.…”
Section: Resultssupporting
confidence: 64%
“…In support of this trend, Okamoto et al [11] found approximately 19-fold higher clarithromycin concentrations in mouse lungs compared to plasma (130.9 Ìg/g vs. 6.8 Ìg/ml) following a 100 mg/kg dose. The clarithromycin concentrations in ELF observed in our study could be an underestimation due to dilutional error inherent in the BAL procedure used.…”
Section: Resultsmentioning
confidence: 52%
“…Nevertheless, the rapid development of antibiotic resistance severely hampers modern medicine and has prompted a search for improved antimicrobial agents. Ketolides, a newer class of macrolides that exhibits a safety profile comparable to that of other antibiotics (15), were shown to be potent in vitro and in vivo against many bacterial strains, including those resistant to drugs such as macrolides-lincosamides-streptogramin B (10,11).…”
mentioning
confidence: 99%
“…While telithromycin has been demonstrated to have in vivo activity in several animal models of infection (3,21,23), limited data which describe the pharmacodynamic profile of this compound against S. pneumoniae are available (Vesga et al, 37th ICAAC). In turn, we evaluated the relationship between telithromycin exposure and outcome by assessing the changes in bacterial density in the pneumococcal thigh infection model.…”
Section: Discussionmentioning
confidence: 99%